PENYELESAIAN PERKARA TINDAK PIDANA KORUPSI DI LUAR PENGADILAN - Maydika Ramadani (2023)
The Criminal Justice System must be reviewed to see wider interests, not only focused on retaliation for perpetrators of criminal acts, but also the interests of victims of criminal acts that deserve attention. The protection contained in the Criminal Procedure Code protects the human rights of perpetrators of criminal acts more than the human rights/interests of victims of criminal acts. The purpose of this research is to find out the settlement of corruption cases outside the court of criminal law policy in carrying out the nature of the settlement of criminal cases outside the court between victims and perpetrators of crime. The normative juridical research method uses statutory approaches, legal comparisons and literature review. The results of the study show that the nature of out-of-court settlements is restorative justice. The system adopted by the Criminal Procedure Code is retributive justice where the point of protection is oriented towards the perpetrator, not restorative justice. Reconceptualization and Coordination in the Criminal Justice System is necessary and very urgent to be carried out, in order to realize law enforcement that is just for all. Keywords : Completion. Corruption Crime. Outside Court.